Development of porous customized Ti-6Al-4V cranial implant manufactured by laser beam powder bed fusion - Eksi Altan, Mihrigul; Acar, Alperen; Ozen, Seyhan; Guldorum, Yeliz; Kulle, Eren; Apaydinli, Berke; Gunay, Abdulkadir; Eryildiz, Meltem (SAGE PUBLICATIONS LTD, 2025)
Customized cranial implants play a crucial role in neurosurgery, serving to restore cranial integrity and protect the underlying brain tissue after trauma or surgical intervention. Ti-6Al-4V cranial implants exhibit high mechanical strength; however, their solid forms can be excessively heavy and possess a high elastic modulus, leading to stress shielding effects. This study focuses on designing a cranial implant utilizing computer tomography data, incorporating different lattice and porous structures to optimize weight and mechanical performance. The analysis, conducted with nTop software, compared displacement and von Mises stress values across different structures. The isotruss lattice structure emerged as the most effective, achieving a weight reduction of approximately 50% while maintaining a von Mises stress of 40 MPa. Following the computational analysis, Laser Beam Powder Bed Fusion (PBF-LB) was employed to fabricate the isotruss implant and the compression test was performed to mimic the cranial implant under realistic conditions. The isotruss lattice cranial implant exhibited a remarkable load-bearing capacity of up to 18,000 N while achieving a 50% weight reduction compared to the solid implant, indicating that this lightweight structure not only offers high-performance load-bearing capabilities but also shows great potential for use in surgical applications.
Keywords: Cranial; porous structure; Ti-6Al-4V; custom implant; additive manufacturing; compression; DESIGN; Engineering